Exploration of Altruistic Behavior in Early Adult Volunteers: A Phenomenological Study - Fadhilah, Dita Noor; Agustin, Rin Widya (Journal of Educational, Health and Community Psychology, 2024)
Altruistic behavior is a conduct that prioritizes the interests of others to alleviate their suffering and enhance well-being without expecting any reward for the actions taken. There are still unanswered questions from previous research regarding the motivations that underlie altruistic behavior in disaster relief volunteers. This study aims to explore and delve into the motivations behind altruistic behavior in Indonesian Red Cross volunteers. The phenomenological approach is employed in this research, using semi-structured interviews to gather data. The study participants are individuals aged 18 to 25 who are actively involved as Indonesian Red Cross volunteers in the city of Surakarta. The results of the research indicate that the motivations driving altruistic behavior include the desire to help others, a calling for humanity service to God, enrichment of social interaction, and the influence of family or circumstances. Further discussion is elaborated in this manuscript.